The Role of Public Relations and Communications in Achieving the Core Mandate of International Non-Governmental Organizations in Ghana - Tetteh, Linda Apokwo (UniMAC - GIJ, 2020)
The practice of Public Relations has seen much evolution, the case of Ghana not being very different. Much as a lot of work has gone into streamlining the definition and practice of Public Relations, there is still some major gap to be filled in giving Public Relations its rightful place in the corporate environment. The goal of the study therefore is to develop an integrated, non-sequential framework for excellent public relations management for the International Non-Governmental Organisations sector in Ghana. The study empirically analyzes how PR is conceptualized and practiced in relation to the purpose (models) and roles (activities). Design/methodology/approach. The study adopted the qualitative approach to gather views for the purpose. It was found out that PR in Ghana is shaped, to a large extent, by a western ideology. PR is however influenced greatly by strong interpersonal relationships, which is premised largely on the culture of the country. What is obvious is that PR in the INGO sector is not fully strategic. PR practitioners are limited in their ability to make impact due a lack of understanding by management about the purpose of PR and budgetary constraints. The limitations of this research is that the use of a qualitative approach means that the results cannot be generalized. As the study focused on one sector, it will be essential to look at other sectors using a generalized sample.
THESIS